2012
DOI: 10.1136/heartjnl-2012-301627
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes following infection of cardiac implantable electronic devices: a prospective matched cohort study

Abstract: In patients with CIED infection managed by recommended therapy, long-term mortality rates are similar to comparable controls. Independent predictors include patient and disease-related factors, in addition to implantation of right ventricular epicardial pacemakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 32 publications
(40 reference statements)
11
111
3
5
Order By: Relevance
“…74 All-cause mortality following CIED infection is considerable, ranging from 6 % to 35 % at 2 years or longer follow-up, although many deaths are not infection-related. 10,66,70,[74][75][76] In most of these studies, more than 90 % of patients underwent complete CIED removal. Mortality with endocarditis is reported between 24.5 % and 29.0 %, 31,71,77 and CIED infections with endocarditis have a higher mortality than pocket infection.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 All-cause mortality following CIED infection is considerable, ranging from 6 % to 35 % at 2 years or longer follow-up, although many deaths are not infection-related. 10,66,70,[74][75][76] In most of these studies, more than 90 % of patients underwent complete CIED removal. Mortality with endocarditis is reported between 24.5 % and 29.0 %, 31,71,77 and CIED infections with endocarditis have a higher mortality than pocket infection.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
“…Observational studies found that 20-40 % of patients were discharged without CIED re-implantation. 32,66,67 Some patients have developed indication for more complex CIED treatment while others will need no re-implantation at all (e.g. malignancy in patients with prophylactic ICD).…”
Section: Re-implantationmentioning
confidence: 99%
“…4,5,17,[49][50][51][52] Several predictors of long-term mortality have been identified including older age, heart failure, infective endocarditis, renal failure and long-term corticosteroid therapy. 46,53 However, these high mortality rates must be seen in the context of populations with multiple co-morbidities. Indeed, device patients have shown high mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial pacing is an option but has been associated with higher mortality rates. 46 An interesting alternative is temporary pacing using a screw-in pacing lead connected to a re-use can strapped on the skin of the patients, 47,48 the so called 'semi-permanent' pacing (see Figure 5). This approach allows patients to safely await implantation of a new device for the recommended 72 hours to 14 days depending on clinical status.…”
Section: Reimplantation Of a Device After Infectionmentioning
confidence: 99%
“…15,[20][21][22][23][24][25] If patients are pacemaker dependent, a temporary pacer is placed at or before the time of exchange. 15,23 Reimplantation of devices, if necessary, depends on the location of the infection. Preferably, the pacemaker should be placed on Treatment of Infected Cardiac Implantable Electronic Devices Fakhro et al 63…”
Section: Pacemakersmentioning
confidence: 99%